Psychological Development and Children's Academic Achievement: A Study of the Impact of Broken Homes - Syamsidar, Syamsidar; Al’Adawiya, Rabiah; Putri, Melda Rahmadani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to deeply understand the impact of broken homes on children's psychological development and academic achievement and to identify various factors contributing to the condition. The method used in this study is descriptive qualitative, with data collection techniques including in-depth interviews, direct observation, and documentation. This research was conducted in Kampung Beru Hamlet, Balangloe Village, South Sulawesi Province. The subjects in this study consisted of seven children (students) from broken homes, each with different backgrounds and experiences. The results indicate that most children from broken homes experience various negative psychological impacts, such as deep loneliness, low self-esteem, excessive anxiety, a tendency to be aggressive, and social withdrawal. These children generally have difficulty establishing healthy and stable social relationships. However, there are also some children who show high resilience or mental toughness and maintain a favorable spirit of learning despite being in a disharmonious family environment. The main factors causing broken homes in the cases studied included unresolved domestic conflict, poor communication, differences in principles between husband and wife, economic and emotional stress, neglect due to work commitments, and the loss of a spouse through death. The results of this study are expected to serve as a reflection and reference for parents, educators, and the community in creating a healthy, supportive, and child-friendly environment to ensure optimal psychological development.